Study of heuristic bias and herding financial behavior model on sharia-based investment decisions for millennial generation - Abdul Rozak; Tiara Felinda Amalia (Institute of Computer Science (IOCS), 2023)
Business activities that run well and safely will increase the rate of economic growth. Relatively affordable investment capital as launched by Indonesia Stock Exchange since 2015 by holding the